Maternal Nutrition and Offspring Stress Response—Implications for Future Development of Non-Communicable Disease: A Perspective From India - Krishnaveni, Ghattu V.; Srinivasan, Krishnamachari (Frontiers in Psychiatry, 2019)
Psychological stress is recognised as a major modifiable risk factor for adult non-communicable disease (NCD) that includes depression, type 2 diabetes mellitus and cardiovascular disease. Dysregulation of hypothalamic-pituitary-adrenal (HPA) axis activity resulting in either exaggerated or blunted cortisol responses, and altered autonomic cardiovascular control have been thought to underlie this association. The developmental origins hypothesis proposes that impaired nutrition during fetal and early postnatal growth is associated with a higher NCD risk later in life. Maternal nutrients are vital for fetal growth and development, and both maternal undernutrition and over nutrition as in the case of gestational diabetes are associated with higher NCD risk markers in the offspring. Recent studies suggest that foetal exposure to maternal nutritional imbalances may permanently alter cortisol and cardio-sympathetic stress-responsiveness, which may link early life nutrition with adult disease risk. A few recent studies that examined the association between low birth weight as a marker of fetal undernutrition and stress response in humans showed that lower birth weight was associated with altered HPA axis and cardiovascular sympathetic nervous system responses to stress in adults as well as children. In addition, altered stress responses in relation to gestational diabetes have been noted. In this paper we present available evidence from India for the association between maternal nutrition and offspring stress responsiveness against the backdrop of global evidence, and discuss its role in the escalating NCD rates in this population. We also discuss the scope for future studies in India and other transitioning countries in this area.